The Effect of Supervised Exercise, Home Based Exercise and Endovascular Revascularisation on Physical Activity in Patients With Intermittent Claudication: A Network Meta-analysis. (September 2019) - van den Houten, Marijn M.L.; Hageman, David; Gommans, Lindy N.M.; Kleijnen, Jos; Scheltinga, Marc R.M.; Teijink, Joep A.W.
Abstract : Background: It is unclear whether supervised exercise therapy (SET), home based exercise therapy (HBET), and endovascular revascularisation (ER) for intermittent claudication (IC) have a meaningful impact on physical activity, despite extensive research on their effect on walking performance. Methods: Multiple databases were searched systematically up to May 2018 for randomised controlled trials with objective measurements of physical activity in patients with IC. A Bayesian network meta-analysis was performed comparing the change in physical activity between baseline and follow up between treatments (SET, HBET, ER) and control (usual care). The standardised mean difference (SMD) with 95% credible interval (CI) was calculated as a summary statistic and converted into steps per day to aid interpretation. Results: Eight trials involving 656 patients with IC investigating the short-term effect of treatment on daily physical activity were included. Both SET (SMD 0.41, 95% CI 0.10–0.72: this corresponds to a difference of + 803 steps/day on a pedometer) and HBET (SMD 0.50, 95% CI 0.18–0.88: + 980 steps/day) displayed a benefit over control, based on evidence of moderate and low quality, respectively. The benefit of ER compared with control was SMD 0.36 (95% CI –0.22 to 0.99: + 705 steps/day), but only one trial supplied direct evidence, resulting in a low rating of the quality of evidence. Comparisons between treatments yielded no statistically significant differences. The results were robust to several sensitivity analyses. Conclusion: SET improves daily physical activity levels in patients with IC over control. HBET may have a similar benefit, while invasive treatment failed to lead to a statistically significant improvement of physical activity compared with control. However, the underlying quality of evidence for comparisons with ER and HBET is low, impeding definite conclusions.